Using Medicaid claims to construct dental service market areas. - Mayer, M L (1999)
OBJECTIVE: To use Medicaid claims data to construct patient origin-based market areas for dental services and compare constructed market areas with those based on the practice county. DATA SOURCES: North Carolina Medicaid claims, eligibility, and provider files, the Cooperative Health Information Systems' dentist licensure files, and the Log Into North Carolina data. STUDY DESIGN: A visit-level file was created from the Medicaid claims data and aggregated by provider practice county and patient county of residence. Using the aggregated file and an algorithm based on the Elzinga-Hogarty approach, patient travel patterns were used to construct mutually exclusive patient origin market areas. DATA ANALYSIS: Market area characteristics were compared across definitions using Pearson correlation coefficients. In addition, estimations of provider participation were performed using market area characteristics as control variables. The beta coefficients associated with market area characteristics were compared across market area definitions. PRINCIPAL FINDINGS: Medicaid claims data, when combined with provider licensure files, can be used to construct market areas based on patient origin data. However, measures of market area characteristics are correlated highly between the two types of market areas studied. Furthermore, beta coefficients on market area variables in models of provider participation are similar in sign, significance, and magnitude across market definitions. CONCLUSIONS: Compared with market areas constructed using patient origin data, county-based market areas adequately proxy for dental markets. Using the county as the market area also avoids the time and computational costs associated with using a patient origin-based approach and facilitates the use of widely available data.